2017
DOI: 10.1016/j.outlook.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of behavioral and psychological symptoms of dementia: A scoping review of the evidence

Abstract: Research and policy implications are relevant to the National Plan to Address Alzheimer's Disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
115
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(118 citation statements)
references
References 96 publications
1
115
0
2
Order By: Relevance
“…The theory of caritative leadership informs both administrative and practical operations in such a way that caregivers can develop and prevent patients’ suffering (Bondas, ). Effective intervention is necessary to prevent aggressive behaviour and reduce caregivers burden (Kolanowski et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The theory of caritative leadership informs both administrative and practical operations in such a way that caregivers can develop and prevent patients’ suffering (Bondas, ). Effective intervention is necessary to prevent aggressive behaviour and reduce caregivers burden (Kolanowski et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…pituitary adenomas release excess ACTH thereby chronically elevating circulating Cort, resulting in Cushing's disease; Boscaro et al, 2001 ). The recent extensive dissection of the neural circuitry that mediates behavioral and hormonal stress responses has uncovered a plethora of brain regions in which disease-associated dysfunction can produce neuropsychiatric symptoms, particularly in the context of neurodegeneration ( Kolanowski et al, 2017 ; Ross et al, 2017 ).…”
Section: The Relationship Between Stress and Neurodegenerative Diseasmentioning
confidence: 99%
“…These symptoms form clusters and four NPS subsyndromes: hyperactivity, psychosis, affective symptoms, and apathy, have been identified [8]. NPS have been associated with severity of cognitive impairments and declining functional abilities [9]. Several studies have also shown that having NPS impairs quality of life [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%